Holding on to voters in volatile times: Bonding voters through party links with civil society. (March 2022) - Martin, Nick; de Lange, Sarah L; van der Brug, Wouter
Political parties are increasingly confronted with electoral volatility. However, the support for some parties is more stable than that of others. Although it has been established that parties' links to civil society stabilised their electorates in the period until the 1980s, it has not yet been investigated whether such links still fulfil this function in our volatile age. In this paper, we argue that traditional party connections, as well as links to modern day civil society organisations, continue to tie voters to parties. Using a novel dataset covering 149 parties in 29 elections in 14 West European countries, we establish that parties with stronger links to civil society do indeed have a more stable support base. This relationship holds for parties of the left and right. Our results demonstrate that parties' societal embeddedness continues to play a role in understanding party competition in the 21st century.